Amphibian skin glands secretions affect plasma coagulation tests - Udovychenko, Iryna; Dudkina, Yuliia; Oliinyk, Denys; Oskyrko, Oleksandra; Marushchak, Oleksii; Halenova, Tetiana (ScienceRise: Biological Science, 2018)
According to the extremely high mortality and disability rates associated with the abnormal functioning of the hemostasis system, the search for new approaches for the prevention and treatment of these conditions is one of the most acute problems of modern biochemistry. The active components of reptile poisons are actively used in the treatment of these diseases, but the study of the effects of amphibians’ skin glands secretion on the functioning of hemostasis system has not yet been carried out. So, the aim of this work was to assess the effects of the components of amphibian skin secretions on the functioning of the coagulation link of the hemostasis system. Methods. In this study the skin secretions of ten Ukrainian species of amphibians were collected: B. bombina, B. variegata, B. bufo, B. viridis, R. temporaria, P. ridibundus, P. esculentus, P. fuscus, S. salamandra and the hybrid of B. bombina and B. variegatа. The samples of crude skin secretions were prepared. The activated partial thromboplastin time (aPTT), thrombin time (TT) and prothrombin time (PT) tests were conducted in vitro using the coagulation analyzer (Rayto RT-2201C, China) and the standard set of reagents (RENAM, Russian Federation). Results. It was established that the components of crude skin secretions of B. bombina, B. variegata, their hybrid, R. temporaria and P. ridibundus prolonged the aPTT of clotting plug formation. The components of skin secretions of B. viridis, P. esculentus, P. fuscus and S. salamandra prolonged the TT of clotting plug formation. Conclusions. The fact that some amphibian species prolonged the aPTT and TT of clotting plug formation could be the indicator of the presence of inhibitors of certain factors of coagulation hemostasis or be the reason of the degradation of the components of coagulation hemostasis by active components of skin secretion. Such results prove that the amphibian crude skin secretions are a potential source of the compounds that can affect the hemostasis system. The identification of an active component and the elaboration of its mechanism of action are required in further investigations